The Effect of Government Expenditure in The Education, Health and Capital Expenditure Sectors on Poverty - Adi Maulana Rachman; Ni Luh Putu Nita Yulianti; Okto Irianto; Elly Noer; Romualdus T.P.M.Djanggo; Fenty Y. Manuhutu; Esy Delia Lewaherilla; Agustinus Fangohoy; Marthen A. I. Nauhumury (Bulletin of Pedagogical Research, 2025)
This study aims to analyze the effect of government spending in the education and health sectors, the labor force participation rate (TPAK), and Gross Regional Domestic Product (GRDP) on poverty in Indonesia during the period 2010–2014. Poverty is a complex socioeconomic problem arising from individuals’ inability to meet basic needs, which in turn limits access to essential services such as education and health. In this study, poverty is treated as the dependent variable, while government expenditure on education and health, TPAK, and GRDP serve as the independent variables. The contribution of this study lies in providing empirical evidence on the relative importance of social sector spending and economic factors in reducing poverty at the regional level in Indonesia. The findings are expected to enrich the existing literature on poverty alleviation and serve as a reference for policymakers in designing more effective and targeted poverty reduction strategies